Experimental analysis on friction-induced vibration of water-lubricated bearings in a submarine propulsion system. (1st May 2020) - Hongling, Qin; Chang, Yang; Hefa, Zhu; Xufei, Li; Zhixiong, Li; Xiang, Xu
Abstract: Abnormal vibration and noise, originated from friction and wear, are often found in water-lubricated stern-tube bearings, which seriously threatens the safety and concealment of underwater vehicles. In order to better understand the friction-induced vibration in water-lubricated stern-tube bearings, friction pairs of rubber specimens matched with ZQSn10-2 brass were tested on the water-lubricated bearing test rig SBB-100. A high-speed camera was used to track the micro images that focused on of the rubber layer vibration motion, while a machine vision technique also was employed to extract the friction-induced vibration of the test bearings. The experimental analysis results demonstrate that the bearing vibration was mainly induced by stick-slip. Furthermore, the orthogonal experiment method was used to distinguish the key factors that induce the bearing vibration among rotating speed, contact pressure, rubber layer hardness and thickness, and lubrication condition. The analysis results indicate that the importance of factors is sorted in the order of lubrication condition, contact pressure, hardness and thickness of rubber layers. In normal lubrication condition, the intensity of friction-induced vibration of the rubber bearings can be reduced by increasing the hardness of the rubber layer, decreasing the contact pressure, and the thickness of the rubber layer. Highlights: Orthogonal experiment tests have been performed for water-lubricated bearings. Key factors for friction-induced vibration are analysed. Stick-slip is the mechanism of water-lubricated bearing vibration. An optimal operating parameter set is presented for the water-lubricated bearings.